(untitled) (Research, Society and Development, 2020)
Low-level laser irradiation (LLLI) modulates several biological processes such as cell proliferation and differentiation, stimulating tissue healing. The objective was to evaluate, through a histomorphometric analysis, the osteogenesis process in defects made in the skull of rats filled with biomaterials and submitted to infrared laser radiation (GaAIAs). Thirty male Wistar rats were used, whose weight varied between 250gr and 300gr, randomly distributed in 2 groups, Test Group (GT) and Control Group (CG). Both groups had 3 observation times, 7, 14 and 21 days, forming 6 subgroups. Two 4mm diameter defects were made in the parietal bones and one of the cavities was grafted with the biomaterial α-TCP and the other with β-TCP / HA. The test groups received low-level laser therapy (LLLI), in infrared spectrum (λ = 830nm, 2 J/cm2, 90mW, 27s). In the control groups, the entire surgical protocol was performed, but without laser application. The laser therapy protocol was established every 48 hours, starting immediately after the surgery and continuing in intervals until the sixth postoperative day. The animals were sacrificed on the 7th, 14th and 21st days. Histomorphometric analysis showed that there is positive bone biomodulation evidenced in the test groups, with a significant result in 21 days. The test group with β-TCP / HA, showed a larger area of bone trabeculae than the control groups. It can be concluded that laser therapy, in the established protocol, acts as a bone biomodulator, stimulating osteogenesis in the grafted areas, and can be used as an adjuvant in the bone repair process.